Penyusunan Portofolio Kampung Pendidikan Arek Surabaya - Yesa Cahayaning; Asmara Indahingwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Parenting patterns depend on how a family environment forms rules (behavior, norms and values) that must be obeyed by family members. This parenting pattern is formed by parents consisting of fathers and mothers to provide education to their children so that it can imprint on the child and make characteristics and personal for the child. So the mayor of Surabaya held the Kampung'e Arek Suroboyo education village competition which was one of the Surabaya City Government's programs in promoting the development of the quality of human resources (HR). Thus mandating "the community is obliged and responsible for the protection of children through the activities of the community's role in the implementation of child protection. The conclusion of this community service activity is the creation of this Education Village aims to create an educational, safe, comfortable, friendly, healthy, creative, creative environment and literacy for the child's growth and development process in community support that guarantees the fulfillment of children's rights and seeks optimal child protection